Analysis and Design of a New Non-Isolated Three-Port Converter With High Voltage Gain for Renewable Energy Applications - Peng Luo; Lei Guo; Jinqiang Xu; Xiaoning Li (IEEE Access, 2021)
This paper proposes a non-isolated three-port converter which integrates the input port, battery port, and load port into one converter for renewable energy applications. The coupled inductor and switched capacitor are used to achieve high voltage gain and three power switches can be utilized to realize the power flows between the sources, the battery, and the load. The energy stored in the leakage inductance is recycled to reduce the voltage stress of the power switch. In addition, various operating stages are analyzed and design considerations are presented. Compared to the relevant converters, the proposed converter can realize power flows and achieve high voltage gain by using few components. Finally, a laboratory prototype of the proposed converter with input port voltage 24 V, battery port voltage 48 V, and output voltage 400 V with 200 W rated power is implemented to validate the feasibility and effectiveness of the theoretical analyses.